Consumer perception of food variety in the UK: an exploratory mixed-methods analysis - Rochelle Embling (BMC Public Health, 2020)
Background: ‘Food variety’ is a key term that is frequently used in dietary guidelines around the world. Consuming a variety of foods – be it within a meal, across meals, or as part of the whole diet – is one factor that has been shown to increase food intake. However, little is known about consumer understanding of variety, and this may be a potential barrier to the success of dietary guidelines in today’s ‘obesogenic’ environment. This research sought to explore 1) consumer recognition of different forms of variety, and 2) consumer definitions of variety. Methods: In an online study (N = 240), participants were asked to discuss a range of photographs depicting different forms of variety, and to directly define the term ‘food variety’. They were unaware of the research aim. Results: Using a mixed methods approach, directed content analysis of these data showed that individuals referenced multiple forms of variety in the presence of food photographs. However, when asked to define variety, participants tended to only discuss variety in the context of the whole diet. Conclusions: These findings emphasise a need to educate consumers about variety to encourage adherence to dietary guidelines and help consumers better manage their own food intake.